2015
DOI: 10.2147/ppa.s82844
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic and shared decision-making preferences among adolescents in Malaysia

Abstract: BackgroundThe purpose of this study was to establish baseline information on the current level of knowledge about, attitude toward, and experience with antibiotic usage, and preferences for shared decision making among adolescents in Malaysia.MethodsA cross-sectional survey, involving 1,105 respondents who were aged between 13 and 17 years and who lived in Malaysia, was conducted using a validated questionnaire. The survey assessed knowledge, attitude, and experience with regard to antibiotic usage, and adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
(33 reference statements)
1
3
0
Order By: Relevance
“…Regarding control preference profiles, our sample not only displays a distribution that pretty nicely reflects the (‘bell’) distribution that has been repeatedly reported in the literature [ 36 38 ], but also specifically resemble CPS profiles reported in studies on men’s’ preferences for involvement in cancer care decisions. In this regard, it is remarkable that, if comparing to Degner and Sloan’s 27 year old data from the ‘pre-patient-involvement-era’, it appears that control preference figures have generally changed in favor of a more collaborative or active role [ 38 , 39 ].…”
Section: Discussionsupporting
confidence: 77%
“…Regarding control preference profiles, our sample not only displays a distribution that pretty nicely reflects the (‘bell’) distribution that has been repeatedly reported in the literature [ 36 38 ], but also specifically resemble CPS profiles reported in studies on men’s’ preferences for involvement in cancer care decisions. In this regard, it is remarkable that, if comparing to Degner and Sloan’s 27 year old data from the ‘pre-patient-involvement-era’, it appears that control preference figures have generally changed in favor of a more collaborative or active role [ 38 , 39 ].…”
Section: Discussionsupporting
confidence: 77%
“…However, this was inconsistent with a similar study by Hassali et al (2017), where the attitude towards the usage of antibiotics was significantly associated with the race among young Malaysian adults. A similar study presented a statistically significant attitude towards antibiotics use among Malay and Indian adolescence compared with Chinese and other races (Ngadimon, 2015). No statistical significance on race could be related to not equally distributed ethnicity distribution, as suggested by Ying et al (2018).…”
Section: Discussionmentioning
confidence: 58%
“…Pharmacists from South Africa reported that most of their clients do not know the product names but they could identify and describe the requested medication based on their colour, appearance and packaging (Tara Carney et al, 2016). A study in Malaysia among secondary students reported low level of knowledge (71•13 %) about antibiotic usage however high knowledge scores were associated with a more negative experience with antibiotic usage (Wati Ngadimon et al, 2015).…”
Section: Knowledge Attitude and Awarenessmentioning
confidence: 99%
“…Several studies showed low level of education, lack of knowledge and lack of awareness as contributing factors for inappropriate medication usage (Gu et al, 2015;Jaber et al, 2015;Wati Ngadimon, Islahudin, Hatah, Mohamed Shah, & Makmor-Bakry, 2015;Yong-Kang, 2018). For instance, Chinese students with lower knowledge scores were more likely to self-medicate with antibiotics, to consult a medical professional when sick with self-limiting illnesses, to be prescribed antibiotics and to request the health care provider to prescribe antibiotics if the health care provider initially was unwilling when compared with students with higher knowledge (X.…”
Section: Knowledge Attitude and Awarenessmentioning
confidence: 99%